2016
DOI: 10.1371/journal.pone.0153673
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Spatial Prediction of Soil Organic Carbon Stocks in a Complex Tropical Mountain Landscape by Methodological Specifications in Machine Learning Approaches

Abstract: Tropical forests are significant carbon sinks and their soils’ carbon storage potential is immense. However, little is known about the soil organic carbon (SOC) stocks of tropical mountain areas whose complex soil-landscape and difficult accessibility pose a challenge to spatial analysis. The choice of methodology for spatial prediction is of high importance to improve the expected poor model results in case of low predictor-response correlations. Four aspects were considered to improve model performance in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 63 publications
1
35
0
5
Order By: Relevance
“…Non-parametric models such as RFR, SVM and SGB have been found superior to MLR due to their ability to handle non-linear relations and multi-source data [17,80,83]. In general, many studies reported RFR as providing better predictions compared to SVM [29,8486]. However, Were et al [87] found SVM as best predictor for the spatial distribution of SOC stock compared to RFR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-parametric models such as RFR, SVM and SGB have been found superior to MLR due to their ability to handle non-linear relations and multi-source data [17,80,83]. In general, many studies reported RFR as providing better predictions compared to SVM [29,8486]. However, Were et al [87] found SVM as best predictor for the spatial distribution of SOC stock compared to RFR.…”
Section: Resultsmentioning
confidence: 99%
“…Four statistical methods which have proved their suitability for digital soil mapping in previous studies—multiple linear (MLR), random forest regression (RFR), support vector machine (SVM) and stochastic gradient boosting (SGB) [2629] were explored to ascertain the most suitable method for high resolution RS data in the study region. Comparison of the traditional regression method (MLR) and different machine learning methods to spatially predict soil properties in West Africa are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of regression modeling approaches with geostatistics of independent model residuals (i.e., regression kriging) is a combined strategy that has been widely used to map SOC (Hengl et al, 2004;Mishra et al, 2009;Marchetti et al, 2012;Kumar et al, 2012;Peng et al, 2013;Adhikari et al, 2014;Yigini and Panagos, 2016;Nussbaum et al, 2014;Mondal et al, 2017). Machine learning algorithms such as random forests or support vector machines have also been used to increase statistical accuracy of soil carbon models (Martin et al, 2011;Hashimoto et al, 2017;Hengl et al, 2017) including applications for SOC mapping (Grimm et al, 2008;Sreenivas et al, 2016;Yang et al, 2016;Hengl et al, 2017;Delgado-Baquerizo et al, 2017;Ließ et al, 2016;Viscarra Rossel et al, 2014). Machine learning methods do not necessarily allow to extract information about the main effects of prediction factors in the response variable (e.g., SOC); consequently, a variable selection strategy is always useful to increase the interpretability of machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…carbon models (Martin et al, 2011;Hashimoto et al, 2017;Hengl et al, 2017) including applications for SOC mapping (Grimm et al, 2008;Sreenivas et al, 2016;Yang et al, 2016;Hengl et al, 2017;Delgado-Baquerizo et al, 2017;Ließ et al, 2016;Viscarra Rossel et al, 2014).Machine learning methods do not necessarily allow to extract information about the main effects of prediction factors in the response variable (e.g., SOC); consequently, a selection strategy is always useful to increase the interpretability of machine learning algorithms. With this diversity of approaches one constant question is if there is a 5 method that systematically improve the prediction capacity of the others aiming to predict SOC across large geographic areas (e.g., Latin America).…”
mentioning
confidence: 99%